Pengaruh Disiplin Kerja, Komitmen Organisasi dan Person Job Fit Terhadap Kinerja Karyawan Pada Sektor Industri Mebel di CV Gardenia Java Ngabul Jepara - Agustina, Sinta; Prawitasari, Dian; Oktavia, Vicky; Wibowo, Mochammad Eric Suryakencana (Jurnal EMT KITA, 2024)
Companies are expected to be able to maximise the limited human resources they have in order to meet the goals of a company that has been set. The purpose of this study is to determine the variable influence of work discipline, organisational commitment, and person job fit on employee performance at CV Gardenia Java.  The research method used is quantitative method. The object of research is one of the furniture industries in Jepara. The population in this study were employees in the production department with a total of 105 people. The data collection technique used was a questionnaire. Data analysis using multiple linear regression with the help of the SPSS 25 application. In analysing data using statistical methods using validity, reliability, and normality tests. To ascertain whether the data meets the basic assumptions of the study, a classic assumption test is carried out. In addition, researchers will conduct multicollinearity, heteroscedasticity, T test, simultaneous test (F), and determination test.  The results of this study indicate that: (1) Work discipline variable has a positive influence on employee performance as indicated by the b1 value (work discipline coefficient value) of 0.678 which means that the more work discipline increases, the employee performance will increase; (2) Organisational commitment variable has a positive influence on employee performance satisfaction, that is, if organisational commitment increases, employee performance will increase. This is indicated by the coefficient value of organisational commitment (b2) of 0.478; (3) The person job fit variable has a positive influence on employee performance as indicated by the person job fit coefficient value of 0.561 (b3). This means that if person job fit becomes more affordable, employee performance will increase.